CYANIDE REDUCTION IN CASSAVA ROOT PRODUCTS THROUGH PROCESSING AND SELECTION OF CULTIVARS IN RELATION TO FOOD SAFETY - Ginting, Erliana; Widodo, yudi (Buletin Palawija, 2013)
About 47% of cassava production in Indonesia was used for human consumption, both as a staple food and snacks. In terms of food safety, the natural presence of cyanogenic glucosides in cassava roots is of concern as they may release free cyanide (HCN), which is highly toxic. At high levels, it may cause acute poisoning, leading to death as well as iodine deficiency and neurological disorders for long-term ingestion. The cyanogenic glucosides content in different cultivars of cassava varied from 1 up to >1,000 mg HCN/kg fresh weight, while 10 mg HCN/kg dry weight was considered to be the safe level for consumption. Various processing methods were reported to be effective in reducing the cyanide content in cassava products. A decrease of 25-50% was observed during overnight soaking, while it was much higher (81%) when subsequent drying and milling into flour was performed. During boiling, steaming, deep-frying, baking and fermentation, a reduction of 45-50%, 17%, 13%, 14% and 38-84% was noted, respectively. Crushing the fresh roots and subsequent sun-drying was the most effective method with >95% of HCN removal. It suggests that low cyanide content of cassava cultivars (mostly sweet/local varieties) are obviously required for direct consumption purposes. This is particularly important for traditional food processors to be selective in obtaining fresh cassava as raw material and choosing proper processing methods. While for gaplek, starch, flour, and mocaf purposes, where washing, soaking, shredding, fermentation, pressing, drying and milling were involved, the bitter cultivars (mostly improved varieties) with relatively high cyanide content can be used. Therefore, breeding selection for cassava cultivars with low cyanide content and high potential yield is essentially needed. Selected improved varieties and promising clones seem to meet this criteria. Regulation for food industries to provide information on cyanide level in cassava food labels would also protect the consumers and promote safe cassava foods.